2020
DOI: 10.48550/arxiv.2004.01140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Skew characters and cyclic sieving

Abstract: In 2010, B. Rhoades proved that promotion together with the fakedegree polynomial associated with rectangular standard Young tableaux give an instance of the cyclic sieving phenomenon.We extend this result to all skew standard Young tableaux where the fakedegree polynomial evaluates to nonnegative integers at roots of unity, albeit without being able to specify an explicit group action. Put differently, we determine in which cases a skew character of the symmetric group carries a permutation representation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Finally, a different approach would be to keep the Kostka-Foulkes polynomials, and replace promotion with a different group action. In [APRU20], it is shown that the set of standard Young tableaux of shape mλ := (mλ 1 , mλ 2 , . .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a different approach would be to keep the Kostka-Foulkes polynomials, and replace promotion with a different group action. In [APRU20], it is shown that the set of standard Young tableaux of shape mλ := (mλ 1 , mλ 2 , . .…”
Section: Discussionmentioning
confidence: 99%
“…It can be shown (see e.g., [APRU20]) that ε k (λ/µ) can be given in terms of a skew character, but we do not need that here.…”
Section: By Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…We discuss an open problem regarding the interpolation between type A and type B q-Narayana numbers. This problem is part of a broader set of questions regarding the interplay of cyclic sieving and characters in the symmetric group, see [APRU20]. We argue that the small special case discussed below is interesting in its own right.…”
Section: Narayana Connectionmentioning
confidence: 95%
“…, m}. The cyclic sieving phenomenon about SST m (λ) and pr has drawn big attention from many researchers (see [2,3,4,5,8,21,22,29] for example.) One of the most celebrated researches in this direction was initiated by Rhoades [21].…”
Section: Introductionmentioning
confidence: 99%